Seasonal Changes in Zooplankton Community Structure and Distribution Pattern in the Yellow Sea, China - Shi, Yongqiang; Wang, Jun; Zuo, Tao; Shan, Xiujuan; Jin, Xianshi; Sun, Jianqiang; Yuan, Wei; Pakhomov, Evgeny A. (Frontiers in Marine Science, 2020)
Changes in zooplankton community and distribution have significant influences on fishery resources due to their vital role in the marine food web. Seasonal variations in zooplankton community structure, abundance and biomass of major taxa and distribution pattern in the Yellow Sea, China were analyzed to obtain the current status of secondary production. A total of 73 taxa (mostly at the species level) were recorded with the highest species richness in summer and lowest in spring. The most abundant zooplankton species in all seasons were copepods Oithona similis, Paracalanus sp. and Calanus sinicus. The mean total zooplankton abundance was the highest in spring and followed a declining trend till winter. Cluster analysis identified two distinct zooplankton assemblages geographically found in the deep (> 50 m depth) and shallow regions. Zooplankton in the shallow region had higher abundance and species richness with the exception of winter season. Small copepods exhibited higher biomass in the shallow region but few abundance differences between the two domains. Large copepods (LC) and giant crustaceans (GC) usually had higher biomass in the deep region with the exceptions of LC in spring and GC in summer. Both the abundance and biomass of chaetognaths were significantly higher in the shallow region, where cnidarian abundance was also higher from spring to autumn. Water currents contributed to the transport of zooplankton between the two domains. The high abundance of copepods in the shallow region satisfied the requirements for the larval fish survival from spring to autumn. However, the high abundance of carnivorous zooplankton in summer–autumn may compete with larval fish for prey, and may directly feed on fish larvae.